Controlling the kinetics of self-reproducing micelles by catalyst compartmentalization in a biphasic system - Post, EAJ; Fletcher, SP (American Chemical Society, 2019)
Compartmentalization of reactions is ubiquitous in biochemistry. Self-reproducing lipids are widely studied as chemical models of compartmentalized biological systems. Here, we explore the effect of catalyst location on copper-catalyzed azide-alkyne cycloadditions which drive the self-reproduction of micelles from phase-separated components. Tuning the hydrophilicity of the copper-ligand complex, so that hydro-phobic or -philic catalysts are used in combination with hydro-philic and -phobic coupling partners provides a wide range of reactivity patterns. Analysis of the kinetic data shows that reactions with a hydrophobic catalyst are faster than with a hydrophilic catalyst. Diffusion-ordered spectroscopy experiments suggest compartmentalization of the hydrophobic catalyst inside micelles while the hydrophilic catalyst remains in the bulk aqueous phase. The autocatalytic effects observed can be tuned by varying reactant structure and coupling a hydrophilic alkyne and hydrophobic azide results in a more pronounced autocatalytic effect. We propose and test a model that rationalizes the observations in terms of the phase behavior of the reaction components and catalysts.